2020
DOI: 10.1177/0008417420941782
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Activity and Boredom in the Transition from Homelessness: Two Narratives

Abstract: Background. Few studies have examined boredom and meaningful activity during the transition from homeless to housed, and those that exist are retrospective. Purpose. To prospectively examine how meaningful activities and boredom are experienced during the process of leaving homelessness. Method. Using a mixed-methods case study design, we interviewed 13 homeless participants at baseline using a 92-item quantitative interview, followed by a semi-structured qualitative interview. Two participants were located si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Community integration has been a challenging outcome to target following homelessness (C. A. Marshall et al, 2020 ) likely due to the stigma of mental illness, substance use disorder and/or homelessness faced by this population (Dej, 2020 ; Forchuk & Csiernik, 2021 ). Further, participants in this study and in previous research have identified that meaningful activity engagement is a frequent challenge following homelessness (C. A. Marshall et al, 2018 , 2020 ; Marshall, Gewurtz, et al, 2022 ), and a pathway to community integration (C. A. Marshall et al, 2022 , 2022 ). Service providers may consider finding ways of intentionally targeting these constructs in the development of goals with persons who experience homelessness and integrate outcome measurement strategies that can evaluate the effectiveness of these approaches.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Community integration has been a challenging outcome to target following homelessness (C. A. Marshall et al, 2020 ) likely due to the stigma of mental illness, substance use disorder and/or homelessness faced by this population (Dej, 2020 ; Forchuk & Csiernik, 2021 ). Further, participants in this study and in previous research have identified that meaningful activity engagement is a frequent challenge following homelessness (C. A. Marshall et al, 2018 , 2020 ; Marshall, Gewurtz, et al, 2022 ), and a pathway to community integration (C. A. Marshall et al, 2022 , 2022 ). Service providers may consider finding ways of intentionally targeting these constructs in the development of goals with persons who experience homelessness and integrate outcome measurement strategies that can evaluate the effectiveness of these approaches.…”
Section: Discussionmentioning
confidence: 55%
“…Recent research suggests that many individuals living with mental illness and/or substance use difficulties have a variety of ongoing unmet psychosocial needs after leaving homelessness, even when they receive HF as an intervention. These include ongoing poverty (Gaetz et al, 2016 ), low levels of community integration (Raphael-Greenfield & Gutman, 2015 ), high levels of substance use (Somers et al, 2015 ), ongoing symptoms of mental illness (Gaetz et al, 2016 ), low levels of engagement in meaningful activity (C. A. Marshall et al, 2018 , 2020 ), and food insecurity (Parpouchi et al, 2016 ). Systems that allow for poor adherence to the HF model, that are poorly integrated, that do not adequately account for consumer choice (Oudshoorn, Smith-Carrier, et al, 2021 ), or that target the security and maintenance of a tenancy as a primary indicator of program effectiveness, may contribute to these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, living in extreme poverty in a high‐income country is likely to limit the extent to which a person can compete for employment positions against housed individuals due to a lack of necessary clothing, places to perform adequate self‐care and travel funds to attend job interviews. If a person does secure employment during homelessness, the need to engage in activities to fulfil one's basic needs for food and shelter, combined with the hours of shelters, drop‐in centres and meal programs typically impair their ability to sustain employment over time (Marshall et al, 2017; Marshall, Keogh‐Lim, et al, 2020). Stigma associated with mental illness, substance use disorder, and homelessness are also likely barriers to participating in employment both while a person is attempting to secure a job, and after attaining an employment role (Belcher & DeForge, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Employment gives purpose in life by providing an opportunity for meaningful time use, something that is frequently denied to individuals during and following homelessness (Marshall, Keogh‐Lim, et al, 2020; Marshall, Oudshoorn, et al, 2021; Marshall, Phillips, et al, 2021). The high rates of mental illness among persons who experience homelessness (Fazel et al, 2014; Hossain et al, 2020) coupled with evidence associating increased participation in meaningful activity with enhanced psychosocial well‐being (Marshall, Davidson, et al, 2019; Marshall, Roy, et al, 2019) emphasises the particular importance of employment in the lives of this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation